Morpho-Phylo Taxonomy of Novel Dothideomycetous Fungi Associated With Dead Woody Twigs in Yunnan Province, China - Mortimer, Peter E.; Jeewon, Rajesh; Xu, Jian-Chu; Lumyong, Saisamorn; Wanasinghe, Dhanushka N. (Frontiers in Microbiology, 2021)
Within the field of mycology, the macrofungi have been relatively well-studied when compared to microfungi. More specifically, the diversity and distribution of microfungi inhabiting woody material has not received the same degree of research attention, especially in relatively unexplored regions, such as Yunnan Province, China. To help address this knowledge gap, we collected fungal specimens from different plants at various locations across Yunnan Province. Our investigation led to the discovery of four species that are clearly distinct from extant ones. These taxonomic novelties were recognized based on morphological comparisons coupled with phylogenetic analyses of multiple gene sequences (non-translated loci and protein-coding regions). The monotypic genus Neoheleiosa gen. nov. is introduced in Monoblastiaceae (Monoblastiales) for a woody-based saprobic ascomycete that possesses globose to subglobose or obpyriform ascomata with centric or eccentric, papillate ostioles, an ascomatal wall with thin-walled cells of textura globulosa, cylindric, pedicellate asci with an ocular chamber, and 1-septate, brown, guttulate, longitudinally striated, bicellular ascospores. Neoheleiosa has a close phylogenetic affinity to Heleiosa, nevertheless, it is morphologically dissimilar by its peridium cells and ornamented ascospores. Acrocalymma hongheense and A. yuxiense are described and illustrated as new species in Acrocalymmaceae. Acrocalymma hongheense is introduced with sexual and asexual (coelomycetous) features. The sexual morph is characterized by globose to subglobose, ostiolate ascomata, a peridium with textura angularis cells, cylindric-clavate asci with a furcate to truncate pedicel and an ocular chamber, hyaline, fusiform, 1-septate ascospores which are surrounded by a thick, distinct sheath, and the asexual morph is featured by pycnidial conidiomata, subcylindrical, hyaline, smooth, annelledic, conidiogenous cells, hyaline, guttulate, subcylindrical, aseptate conidia with mucoid ooze at the apex and with a rounded hilum at the base. Acrocalymma yuxiense is phylogenetically distinct from other extant species of Acrocalymma and differs from other taxa in Acrocalymma in having conidia with 3 vertical eusepta. Magnibotryascoma kunmingense sp. nov. is accomodated in Teichosporaceae based on its coelomycetous asexual morph which is characterized by pycnidial, globose to subglobose, papillate conidiomata, enteroblastic, annelledic, discrete, cylindrical to oblong, hyaline conidiogenous cells arising from the inner layer of pycnidium wall, subglobose, oval, guttulate, pale brown and unicelled conidia.